Relationship between pain catastrophization and functional capacity of women with knee osteoarthritis: a cross-sectional study (Research, Society and Development, 2022)
Knee osteoarthritis has pain as its main symptom. Catastrophizing is a cognitive factor that can influence painful sensations. This study aims to evaluate the presence of pain catastrophizing in women with knee osteoarthritis and the relationship of catastrophizing with functional capacity, pain, quality of life, and joint mobility. The sample consisted of women aged 50 to 80 years with knee osteoarthritis. The following were evaluated: Catastrophizing [Pain Catastrophizing Scale (PCS)]; Functional capacity [Tests: Chair-Stand; 40m walk; Stair-Climb]; Quality of life [Western Ontario and McMaster Universities Questionnaire (WOMAC) and Medical Outcomes Study 36 – Item Short-Form Health Survey (SF-36)] and knee joint mobility [goniometry]. According to the PCS result, the sample was divided into groups GCC (With catastrophizing) (n=10) and GSC (Without catastrophizing) (n=23). Mean and standard deviation analysis, Shapiro-Wilk test, Student's t-test or Mann–Whitney U test, and Spearman correlation were performed. It was considered p